Wheat Yield Response to Fungicide Application and Nitrogen Management in Kansas during 2023-2024 - Jorge Romero Soler; Luiz Otavio Pradella; Nicolas Giordano; Jazmin Gastaldi; Giovana Cruppe; Romulo P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2025)
Nitrogen (N) and fungicide are among the more important management tools to increase wheat (Triticum aestivum L.) grain yield in Kansas. However, there is limited information on whether hard red winter wheat grain yield is impacted by the interaction of nitrogen rates and foliar fungicide application. Thus, our objective was to evaluate the effects of different N rates with or without a fungicide application at Feekes 10.5 on grain yield of two winter wheat genotypes with contrasting disease resistances to leaf and stripe rust. Seven field experiments were established in Kansas using a factorial structure of two fungicide management (either absence of fungicide or 13 oz of Nexicor per acre), five N rates (0, 30, 60, 90, and 120 pounds of N per acre), and two genotypes (Larry and Zenda) in a split-split plot design during the 2023-2024 growing season. Depending on the environment, grain yield varied from less than 18 bushels per acre to more than 88 bushels per acre, likely due to differences in initial soil NO₃-N levels and in-season precipitation. A significant interaction was observed between fungicide application and location, with mean yields ranging from 14.0 bushels per acre in Hoisington (with fungicide) to 87.9 bushels per acre in Leoti (without fungicide). Fungicide had a significant effect in half of the locations, with the greatest yield response observed in Ashland Bottoms (8.6 bushels per acre), which also received the highest precipitation during the growing season. Nitrogen rate increased the yield of variety Zenda from 55.1 bushels per acre at the zero nitrogen rate, to 62.5 bushels per acre at the highest rate, and of the wheat variety Larry from 51 to 54 bushels per acre. Results suggested that the management of nitrogen and fungicide were varietyand environment-specific, respectively, supporting the notion of adaptive management based on seasonal conditions.
Keywords: winter wheat; fungicide; nitrogen management